2014
DOI: 10.4102/sajems.v17i2.443
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate social responsibility factors on the competitiveness of small and medium-sized enterprises

Abstract: Corporate social responsibility (CSR) has become increasingly important to the competitiveness of small and medium-sized enterprises (SMEs). A positive relationship between the CSR activities of SMEs and their enhanced competitiveness exists, at least if a long-term perspective is adopted (European Competitiveness Report, 2008:106; Mandl & Dorr, 2007:2). Despite the widespread practical and academic interest in CSR and its impact on the competitiveness of SMEs, few theoretical and empirical contributions coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
2
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(152 citation statements)
references
References 24 publications
10
112
2
14
Order By: Relevance
“…First, the sample was restricted to companies in Spain, which could be seen as a restriction on the generalisability of the results. However, our findings are consistent with the literature and the results of previous studies from non-Spanish samples (Hur et al, 2014;Turyakira et al, 2014), which clearly supports the validity of the present results for companies outside Spain. Second, the technique used to validate the proposed model -structural equation modelling -is a limitation because it assumes the linearity of the relationships between the latent variables (Castro & Roldán, 2013).…”
Section: Discussionsupporting
confidence: 83%
“…First, the sample was restricted to companies in Spain, which could be seen as a restriction on the generalisability of the results. However, our findings are consistent with the literature and the results of previous studies from non-Spanish samples (Hur et al, 2014;Turyakira et al, 2014), which clearly supports the validity of the present results for companies outside Spain. Second, the technique used to validate the proposed model -structural equation modelling -is a limitation because it assumes the linearity of the relationships between the latent variables (Castro & Roldán, 2013).…”
Section: Discussionsupporting
confidence: 83%
“…They established four CSR practices: well-being of employees, ethical issues (related to nepotism and tribalism), corruption, and the natural environment. Similarly, Amaeshi et al [13] and Turyakira, Venter, and Smith [35] reported that CSR practices in SMEs in Sub-Saharan Africa are centred on areas such as the workplace, market place, local community and the natural environment. A number of authors have shown that CSR in Sub-Saharan Africa focus on charity or donations, community involvement, and ethic (e.g., [36][37][38]).…”
Section: Csr In Smesmentioning
confidence: 99%
“…Their findings indicate that perceived social responsibility had a significant effect on firm performance; similarly, perceived ethics positively impacts SMEs performance. Another related study by Turyakira, Venter, and Smith [35] focuses on the relationship between CSR and outcomes (competitiveness). Empirical results indicate that workforce-oriented CSR activities, society-oriented CSR activities, market-oriented CSR activities and regulated oriented CSR activities significantly influence the competitiveness of SMEs in Uganda [35].…”
Section: Csr In Smesmentioning
confidence: 99%
“…These findings support Lee's (2011) institutional and stakeholder theory to explain how firms choose their CSR strategy. Further research linking the different forms of community engagement with company competitiveness is needed, especially that linking more closely with African and South African cases (Turyakira, Venter & Smith, 2014 Research points to four broad dimensions of the partnering relationship that need to be considered in any evaluation process: -The way in which value is created through the form of partnering relationship; -The capacity of partners to establish and implement the partnership; -The outcomes of partnership activities; -Its portfolio performance. (Esteves & Barclay, 2011) …”
Section: Resultsmentioning
confidence: 99%
“…However, from the 1980s onwards, there was a shift from defining CSR to attempting to measure its impact using frameworks and models to guide the creation of CSR strategies. More recently, companies have begun to realise that CSR activities could have a positive impact on financial returns (Williams, 2014) although evidence in South Africa is contradictory (Gladysek & Chipeta, 2010;Turyakira, Venter & Smith, 2014).…”
Section: Corporate Social Responsibility Critiquesmentioning
confidence: 99%